226k views
4 votes
Solve for g.
-3+5+ 6g=11-3g

2 Answers

0 votes

Answer: g = 1

Explanation:

Add/subtract the numbers: -3 + 5 = 2

6g + 2 = 11 - 3g

Subtract 2 from both sides

6g + 2 -2 = 11 - 3g - 2

simplify

6g - -3g + 9

Add 3g to both sides

6g + 3g = -3g + 9 + 3g

simplify

9g = 9

Divide both sides by 9


(9g)/(9) =
(9)/(9)

simplify

g = 1

User Mkhurmi
by
5.7k points
3 votes

Answer:

g=1

Explanation:

First you would combine like terms and get 2+6g=11-3g

Then add 3g to both sides and get 2+9g=11

Then subtract 2 from both sides and get 9g=9

Lastly divide both sides by 9 and get g=1

User Gal Dreiman
by
5.5k points